1987
DOI: 10.1136/hrt.57.5.458
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor T lymphocyte function in patients with idiopathic congestive cardiomyopathy.

Abstract: SUMMARY Suppressor T lymphocyte function was examined in 11 patients with idiopathic congestive cardiomyopathy and in 11 age and sex matched patients with a similar degree of heart failure resulting from ischaemic heart disease. Suppressor T lymphocyte function was also assessed in a control population of 11 normal subjects. Suppressor T lymphocyte function was reduced in both groups of patients with heart failure but not significantly, and a wide range of suppression was demonstrated in all groups.These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
(1 reference statement)
2
3
0
Order By: Relevance
“…Likewise, mice with a deletion of alpha‐beta T lymphocytes had only minimal myocardial damage after coxsackie viral infection . Regarding Tregs, numerous studies reported decreased levels of Tregs and/or suppressed Treg function in patients with myocarditis or idiopathic cardiomyopathies . In the present study, similar blood levels of Tregs (defined as CD4 + CD25 + CD127 low and expressed as% CD3 + T cells) were observed in patients with iDCM and age‐matched patients with stable and chronic ischaemic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 77%
“…Likewise, mice with a deletion of alpha‐beta T lymphocytes had only minimal myocardial damage after coxsackie viral infection . Regarding Tregs, numerous studies reported decreased levels of Tregs and/or suppressed Treg function in patients with myocarditis or idiopathic cardiomyopathies . In the present study, similar blood levels of Tregs (defined as CD4 + CD25 + CD127 low and expressed as% CD3 + T cells) were observed in patients with iDCM and age‐matched patients with stable and chronic ischaemic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 77%
“…We saw a wide range of values in the immune parameters and inflammatory markers in these elderly patients demonstrating diversity or heterogeneity. This is consistent with other investigators who have observed this same phenomenon (wide variability) when studying T-suppressor activity in patients with heart failure [9], Variation in measures of cellular immune function in the elderly is widely reported, and our study is consistent with this observation [30][31][32], It is therefore particularly interesting that in this study we observed a significant correlation between TNF levels and NK activity, such that varia tion in TNF levels accounted for about half the variation in NK activity, and differences in Z)-dimer levels accounted for an additional component of the variation.…”
Section: Discussionsupporting
confidence: 81%
“…The immune system is among these, though its role has not been fully de fined [3], The heart has clearly been shown to be a target organ of immune injury [4][5][6][7], Increased antibodies, immunoglobins, and complement are found in rheumatic heart disease, viral cardiomyopathy, Lyme carditis, SLE, and sarcoid [4], The role of inflamma tion and immune injury in atherosclerosis has been a topic of increasing interest [8]. An association between heart failure and re duced T-lymphocyte suppressor function has recently been documented [9], Reduced natu ral killer (NK) cell cytotoxicity [7,10], dimin ished lymphocyte responsiveness to mitogens [11] and altered T-cell suppressor activity [12] have all been observed in patients with idiopathic dilated cardiomyopathy. An 'im mune hypothesis' for the pathogenesis of di lated cardiomyopathy has been suggested [4], which proposes the following sequence of events: viral infection with resultant T-lym phocyte system activation, lymphocyte infil tration of the myocardium, subsequent myo cyte necrosis, and ultimately progression to heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, Lowry et al reported that there was no defect in suppressor T cell function in patients with congestive cardiomyopathy 35. Whatever the finding is, it is very important to define the suppressor cells according to the specific member markers for assessing the cell subset function.…”
Section: Discussionmentioning
confidence: 99%